PERAMALAN MENGGUNAKAN METODE HOLT-WINTERS UNTUK PENGUJIAN KENDARAAN BERMOTOR (STUDI KASUS: PENGUJIAN KENDARAAN BERMOTOR KABUPATEN TABANAN) - Masyuni, Ida Ayu; Dharma, Agus; Gunantara, Nyoman (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i03.p04, 2019)
Vehicle inspection is made to guarantee the safety of vehicle on the road. Vehicle Inspection held regularly, in order to reduced any accident that is caused by the trouble or damage of the ma-chine. Vehicle Inspection Unit is expected to give the best service to the customer. The Unit has to be ready in every aspect of inspection such as inspection book, sticker, inspection plate, human re-sources and the possibilities in increasing the amount of equipment. Forecasting method can be used for planning all the item mentioned above. The forecasting methods that is used in this paper is Holt-Winters Model. In addition, we can predict the amount of vehicle to be inspected 12 month ahead, so the unit can analyze and plan the needs of vehicle inspection operation. The used of Holt-Winters Model Method, , produced Mean Absolute Percentage Error (MAPE) of 1.09%.This indicated that the model produced good values of prediction, which can be used to maximize the vehicle inspection, especially in Tabanan Regency.